Psychometric properties and standardization of the shortened latvian personality inventory (LPI-v3s) in athlete sample: Implications for evidence-based assessment - Katrina Volgemute; Viktorija Perepjolkina; Gundega Ulme; Agita Abele; Kristers Ansons; Renars Licis; Rodrigo Lavins; Alina Klonova (PLoS ONE, 2026)
Background and objective Personality traits are relevant to sport participation and athlete development. Many personality measures used in sport lack systematic psychometric evaluation within athletic populations and are rarely accompanied by population-appropriate normative references. The present research comprised two interlinked studies aimed at empirically examining and refining a shortened version of the Latvian Personality Inventory (LPI-v3s) for use in athlete samples, and at exploring associations between personality traits and sport achievement status. Methods A total of 925 athletes (aged 15–45 years) representing 84 sports participated in the study. Following data screening, two subsamples were formed: Study 1 ( n = 436) for psychometric evaluation and norm development, and Study 2 ( n = 753) for exploratory criterion-related analyses. In Study 1, exploratory and confirmatory factor analyses were conducted, and measurement invariance across gender was examined using multigroup CFA. Continuous regression-based norming procedures were applied to derive age- and gender-specific T-scores. In Study 2, hierarchical binary logistic regression was used to explore associations between personality traits and competitive status (elite/pre-elite vs. non-elite). Results The resulting 53-item LPI-v3s demonstrated an interpretable five-factor structure comprising 14 trait scales, acceptable to good internal consistency (α = 0.72–0.88), and configural, metric, and scalar invariance across gender groups. Exploratory hierarchical binary logistic regression analyses indicated that selected trait-level variables (most notably Anxious Insecurity, Sociability and Orderliness) showed small-to-moderate associations with competitive status, with modest overall classification performance (AUC = 0.64). Conclusions The findings support the internal consistency and measurement adequacy of the LPI-v3s within this athlete sample and underscore the importance of contextualized, cautious interpretation of personality scores in sport-related research. Given the provisional nature of the factorial structure and the modest predictive performance observed in Study 2, the LPI-v3s may be useful for research and exploratory assessment contexts involving Latvian-speaking athletes, but should not be used as a diagnostic, selection, or talent-identification tool.